2014
DOI: 10.1002/rnj.110
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence and Prostate Cancer: A Progressive Rehabilitation Program Design

Abstract: The improvement in QoL is mediated indirectly by the improvement in the UI symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
9
0
3
Order By: Relevance
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
“…In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set. As for the language of the articles, 16 were published in English, (5,6,8,11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) one in Spanish (7) and one in Portuguese. (23) As for the country where the study was developed, three were developed in Spain, followed by the United States, United Kingdom, Italy, Australia and China, with two studies each, and Brazil, Denmark, Sweden, Norway and The Netherlands, with one study in each country.…”
Section: Resultsmentioning
confidence: 99%
“…Faithfull et al demonstrated that PFMT, in conjunction with bladder retraining, patient education and problem solving and coping strategies, resulted in significant improvement in IPSS (p < 0.005) as well as a positive impact on HRQL after RT treatment (77). Serda et al (86) demonstrated improvements in variables related to the UI symptom, intensity, frequency, difficulty and limitation of activity after 24 weeks of PFMT (p ≤ 0.0001). These results were further confirmed by Dieperink in an RCT of Danish population (n = 161) stratified to multidisciplinary rehabilitation after RT/ADT, where nursing counselling sessions and therapist-guided instructive sessions resulted in significant improvements of LUTS symptoms vs. standard care (75).…”
Section: Pfmt After Radiotherapymentioning
confidence: 96%
“…Harninkontinenz | Zahlreiche RCT-Studien haben den Einfluss von Schließmuskeltraining allein [6] oder in Kombination mit Kräftigungsübungen [20] auf die Harninkontinenz untersucht (▶ Tab. 2).…”
Section: Grundsätze Der Bewegungstherapieunclassified
“…2). Schließmuskeltraining verbessert bei Prostatakrebspatienten im Vergleich zur nicht-trainierenden Kontrollgruppe sowohl vor [11,40] als auch nach der Operation signifikant die Symptome sowie die Art und den Schweregrad der Harninkontinenz [6,20]. Ein 4-wöchiges präoperatives Training führt zu einer kürzeren Inkontinenzzeit als alleiniges postoperatives Training [11].…”
Section: Grundsätze Der Bewegungstherapieunclassified